2017
DOI: 10.1002/ijgo.12335
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial receptivity and conception outcome among women with light menstrual bleeding of unidentified etiology

Abstract: Objective: To investigate endometrial receptivity (ER), conception outcome, and other factors among women with light menstrual bleeding of unidentified etiology. Methods:A prospective study was undertaken at a center in China. Between January 1, 2011, and December 31, 2014, women meeting the inclusion criteria (aged 20-35 years, without any history of pregnancy, desire to conceive, follicle-stimulating hormone <10 IU on second or third day of cycle, and regular menstrual periods) were enrolled. Participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Scanty bleeding is usually an indication that the lining of the uterus is not as lush or thick. Light menstrual periods are also a big sign that the uterine lining is not getting the circulation it needs to really build up to the thickness for an embryo to implant ( 15 , 16 ), and women with light menstrual bleeding are associated with a poor conception outcome ( 17 ). In our current study, we found that there was no difference in the length of the menstrual cycle and menses between women with a history of caesarean scar pregnancy who had or did not have a subsequent pregnancy after unprotected sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Scanty bleeding is usually an indication that the lining of the uterus is not as lush or thick. Light menstrual periods are also a big sign that the uterine lining is not getting the circulation it needs to really build up to the thickness for an embryo to implant ( 15 , 16 ), and women with light menstrual bleeding are associated with a poor conception outcome ( 17 ). In our current study, we found that there was no difference in the length of the menstrual cycle and menses between women with a history of caesarean scar pregnancy who had or did not have a subsequent pregnancy after unprotected sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy menstrual bleeding can be caused by processes interfering endocrine, paracrine and hemostatic functions of the endometrium and the myometrial contractility (e.g., endometrial polyps, adenomyosis, leiomyomas, coagulopathy, hyperplasia, polycystic ovarian syndrome) [ 68 ]. However, light menstrual bleeding sometimes is not clearly attributed to a specific cause [ 69 ]. Reports of heavy bleeding and menstrual blood clots appear to be lower than those identified in previous research [ 18 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…No endometrium peristalsis wave within 3 min; score, 1; c two-dimensional gray-scale mode; endometrial thickness, 6.0 mm; score, 1; endometrial type, type C; score, 1; d 2D color Doppler mode; a little blood flow in the subendometrium; score, 2; e threedimensional mode; EV, 1.56 cm 3 ; score, 1; f three-dimensional mode; VFI, 0.027; score, 2 assessment of endometrial repair, but these features have limitations in the monitoring of disease condition and the diagnosis and treatment of diseases. In recent years, increasing attention has been paid to the role of recovery of endometrial receptivity in the endometrial repair [4,[14][15][16]. Although many studies have been conducted to investigate the endometrial receptivity, the methods in these studies are often different and there are no widely accepted criteria for the assessment of endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have suggested that ultrasound can be used to assess the endometrial receptivity [3]. However, few studies were conducted to evaluate the endometrial receptivity in patients with induced abortion by using ultrasound multimodal score [4]. This study aimed to evaluate the clinical value of ultrasound multimodal score in the evaluation of endometrial receptivity in patients with induced abortion.…”
Section: Introductionmentioning
confidence: 99%